Leur vie d homme presque, d homme tout juste, d homme assez Une étude de l hybridation des créatures beckettiennes dans le contexte de l Anthropocène - Thobois, Céline (My University, 2020)
This article offers a re-contextualisation of Beckett’s creatures in the Anthropocene and the Great Acceleration which leads to the introduction of a new vocabulary in order to conceptualise his hybrid creatures. After the definition of the concepts of the ‘techno-human’ according to Braden R. Allenby and Daniel Sarewitz’s The Techno-Human Condition, this article explores Beckett’s use of technology in Happy Days and Play at artistic, practical and ethical levels, and showing how this paves the way for cybernetic adaptations.
PUBLISHED
Keywords: Samuel Beckett; Anthropocene; Hybridisation; Techno-human; Behaviourism; Ethics; Cybernetics; Creative Arts Practice; Creative Technologies; Anthropocene; Behaviourism; Irish Theatre, Film and Cultural Performance; Posthumanism; posthuman; Culture; Literature